Efficient global maximum power point tracking technique for a partially shaded photovoltaic string. Issue 14 (1st November 2016) - Manickam, Chakkarapani; Raman, Guru Praanesh; Raman, Guru Raghav; Ganesan, Saravana Ilango; Chilakapati, Nagamani
Abstract : Maximum power point tracking (MPPT) is essential for a photovoltaic (PV) system in order to maximise the utilisation of solar energy. Under partially shaded conditions (PSC), PV strings with bypass diodes exhibit multiple peaks in the power–voltage ( P – V ) characteristics. Although various Global MPPT (GMPPT) algorithms have been proposed to address this issue, most of them cannot distinguish between PSC and uniform insolation, leading to the scan of the entire P – V curve under uniform insolation levels. This study introduces a general method to detect the occurrence of PSC in a PV string thereby dispensing the need to scan the entire PV curve under uniform insolation. Further, a simple technique is proposed to determine the GMPP with the minimum possible search space under PSC. The proposed algorithms for the detection of partial shading and GMPPT are validated experimentally.